HUKUM KELUARGA ISLAM DALAM MASYARAKAT MUSLIM DIASPORA DI BARAT (Perspektif Hukum Perdata Internasional) - Wahyuni, Sri (UIN Sunan Kalijaga Yogyakarta, 2014)
This article discusses about application of the Islamic Family Law for the migrant muslims who live in the western countries, such as America, England, Germany and France. This discussion is analyzed in International Private Law theories of Personal Status. Each country will have different application because of the difference of principle in the International Private Law about Personal Status. The Islamic family law is not legally applied for migrant muslims in America and England courts because both are countries which apply common law system. They use the domicile principle in the case of personal status in the International Private Law discourse. Therefore, the muslims migrant society apply the Islamic family law culturally in their community, through an Imam or mufti as their leader and consultant. This application is not legal according to the states law. In the European continent countries which use the civil law system, such as in Germany and France, the Islamic Family law is applied for the migrant muslims society, if it’s compatible to the public order. The court may apply the Islamic family law for the migrant muslims, because both are countries which use the nationality principle for the case of personal status in the International Private Law discourse.